Photography - Kallen, Stuart A., 1955- (Detroit : Thomson Gale, 2007)
An introduction to the history of photography.
A rich history -- A new way to see the world -- A fine art movement -- Capturing the human drama -- Outsiders and experimentation -- Pixels and pictures.
Includes bibliographical references and index.
Keywords: Photography, Artistic -- Juvenile literature; Photography, Artistic